Disparities in the Care of Differentiated Thyroid Cancer in the United States: Exploring the National Cancer Database. Issue 7 (July 2017) - Jaap, Kathryn; Campbell, Rebekah; Dove, James; Fluck, Marcus; Hunsinger, Marie; Wild, Jeffrey; Arora, Tania; Shabahang, Mohsen; Blansfield, Joseph
Differentiated thyroid cancer (DTC) treatment is multifaceted, and may be influenced by socio-economic factors. The goal of this study is to examine disparities in DTC treatment. DTC patients from 1998 to 2012 were identified using the National Cancer Database. DTC was identified in 262, 041 patients. The mean age was 48.2. The majority of patients (52%) received care at Comprehensive Community Cancer Programs (CCCPs). Total thyroidectomy was less common at Community Cancer Programs (CCPs) [odds ratio (OR): 0.735; 95% confidence interval (CI): 0.707–0.764), and more common at academic centers (OR: 1.129; 95% CI: 1.102–1.157) compared with CCCP. A central neck dissection was performed most often at academic center (20.6%) versus CCP (10.0%). Black patients were less likely to undergo central neck dissection compared with white patients (OR: 0.468; 95% CI: 0.452–0.484). Patients more likely to receive radioactive iodine were white compared with black patients (hazard ratio: 0.833; 95% CI: 0.806–0.861), privately insured compared with uninsured patients (hazard ratio: 1.272; 95% CI: 1.210–1.341), and patients treated at CCCP. Disparities exist in DTC treatment. Individuals at risk for under-treatment are black patients, uninsured patients, and those treated at CCP. As the Affordable Care Act changes access to health care, future studies will be needed to readdress disparities.